Ultrastructural and immunocytochemical study of a case of invasive cribriform breast carcinoma. Issue 1 (January 1988) - Wells, C A; Ferguson, D J
Abstract : A case of recurrent invasive cribriform carcinoma of the breast mimicked the histological and mucin staining characteristics of adenoid cystic carcinoma. The diagnosis was based on negative immunocytochemical staining for laminin and ultrastructural evidence of luminal differentiation by cells lining the cystic spaces. Accurate characterisation of this type of breast tumour can be facilitated by retrospective immunocytochemical or ultrastructural examination, or both.